Standardization of diagnostic and prescriptive learning disability evaluation scale (ldes-4) to improve learning quality of students with learning problems - Sara Pazoki; AliAkbar Arjmandnia; Mohsen Shokouhi Yekta; Bazargan Harandi Abbas; Ali MoghaddamZadeh (مجله علوم روانشناختی, 2023)
Background: Considering teachers’ significant role in identifying students with specific learning disabilities (SLDs), it is necessary to develop a native teacher-oriented tool with appropriate validity and reliability, as a basis for related interventions. Aims: This research aimed to standardize the diagnostic-prescriptive Learning Disability Evaluation Scale (LDES-4) (McCarney & House, 2018). Methods: The statistical population comprised second to fifth-grade students studying in 1400-1401. The normative sample group involved 596 students selected by simple random and purposive sampling methods while the clinical sample group involved 27 students with SLD selected by available sampling method. Colorado Learning Difficulties Questionnaire (CLDQ) (Willcutt et al., 2011) was used for concurrent validity. Exploratory Factor Analysis, Structural Equation Modeling, Multiple Linear Regression, and Independent T-Test were utilized for data analysis. Results: A five-component structure was extracted by Principal Axis Factoring and Promax rotation methods. The results were very close to the theoretical structure of the scale and adequately fit with the data. The correlation coefficient between the full-scale scores of the current scale and CLDQ was equal to 0.65 showing acceptable concurrent validity as well as a significant difference between normative and clinical groups (p< 0.001). The internal consistency coefficients were desirable and ranged from 0.97 to 0.99. Moreover, Intraclass Correlation Coefficients (ICC) ranged from 0.88 to 0.97 indicating the temporal stability of the scale. Conclusion: As a result, the Persian version of the Learning Disability Evaluation Scale can be used as a native valid, and reliable tool to diagnose SLD in second to fifth-grade students.